Características psicosociales de una muestra de 2540 personas en procesos de selección de personal que se someten al polígrafo en Latinamerican Polygraph Institute y análisis de las respuestas en cinco preguntas claves del procedimiento (2018)
The use of new technologies to support personnel selection processes in large, medium and small companies has been of great importance to improve these processes. The information provided by these technologies allows to have more data and tools to strengthen the selection process. In the present investigation the polygraph was used, a technology that allows to know the psychophysiological reactions of the body after the presentation of a stimulus, for that matter some questions. The objectives of this study were to establish the psychosocial characteristics of 2540 people who underwent the polygraph in personnel selection processes at the Latinamerican Polygraph Institute, and to analyze five key questions that are asked in the procedure. A relationship was found between the five questions they asked and the results of the polygraph test. In addition, some interesting psychosocial characteristics were found about the consumption of alcohol and marijuana in the examinees.